Asymmetric synthesis of a stereopentade fragment toward latrunculins - Benjamin Joyeux; Antoine Gamet; Nicolas Casaretto; Bastien Nay (Beilstein Journal of Organic Chemistry, 2023)
Latrunculins are marine toxins used in cell biology to block actin polymerization. The development of new synthetic strategies and methods for their synthesis is thus important in order to improve, modulate or control this biological value. The total syntheses found in the literature all target similar disconnections, especially an aldol strategy involving a recurrent 4-acetyl-1,3-thiazolidin-2-one ketone partner. Herein, we describe an alternative disconnection and subsequent stereoselective transformations to construct a stereopentade amenable to latrunculin and analogue synthesis, starting from (+)-β-citronellene. Key stereoselective transformations involve an asymmetric Krische allylation, an aldol reaction under 1,5-anti stereocontrol, and a Tishchenko–Evans reduction accompanied by a peculiar ester transposition, allowing to install key stereogenic centers of the natural products.